PCI compliance : the definitive guide - Bhargav, Abhay (CRC Press, Taylor and Francis, 2014)
Although organizations that store, process, or transmit cardholder information are required to comply with payment card industry standards, most find it extremely challenging to comply with and meet the requirements of these technically rigorous standards. PCI Compliance: The Definitive Guide explains the ins and outs of the payment card industry (PCI) security standards in a manner that is easy to understand. This step-by-step guidebook delves into PCI standards from an implementation standpoint. It begins with a basic introduction to PCI compliance, including its history an.